Forensic Audits in Practice: A Systematic Literature Review - Marnoko Marnoko; Edisah Putra Nainggolan; Ihsan Abdullah (Lembaga Riset Ilmiah, 2026)
This study aims to explore and synthesize literature related to the role of forensic audits in fraud detection and prevention through the Systematic Literature Review (SLR) approach. Article searches were conducted on Scopus, Web of Science, Google Scholar, and JSTOR databases using keywords such as